Computational Insights Into Voltage Dependence of Polyamine Block in a Strong Inwardly Rectifying K+ Channel - Chen, Xingyu; Bründl, Michael; Friesacher, Theres; Stary-Weinzinger, Anna (Frontiers in Pharmacology, 2020)
Inwardly rectifying potassium (KIR) channels play important roles in controlling cellular excitability and K+ ion homeostasis. Under physiological conditions, KIR channels allow large K+ influx at potentials negative to the equilibrium potential of K+ but permit little outward current at potentials positive to the equilibrium potential of K+, due to voltage-dependent block of outward K+ flux by cytoplasmic polyamines. These polycationic molecules enter the KIR channel pore from the intracellular side. They block K+ ion movement through the channel at depolarized potentials, thereby ensuring, for instance, the long plateau phase of the cardiac action potential. Key questions concerning how deeply these charged molecules migrate into the pore and how the steep voltage dependence arises remain unclear. Recent MD simulations on GIRK2 (=Kir3.2) crystal structures have provided unprecedented details concerning the conduction mechanism of a KIR channel. Here, we use MD simulations with applied field to provide detailed insights into voltage dependent block of putrescine, using the conductive state of the strong inwardly rectifying K+ channel GIRK2 as starting point. Our µs long simulations elucidate details about binding sites of putrescine in the pore and suggest that voltage-dependent rectification arises from a dual mechanism.